Success and failure factors in developing new banking and insurance services - Oldenboom, Nicola (My University, 1998)
The development and introduction of new products is essential for a firm's survival. Numerous activities are administered in developing Dew service products. New product development management has control over the proficiency and choice of activities performed. The objectives of this study were to discover the factors that underlie the proficiency and development activities performed, and to see which are prone to lead a new service to success or result in failure. Unique characteristics of services suggest a different emphasis on development activities than are normally associated with the development of goods. Any differences in factors between the sample of banks and insurers were also investigated. Results from a self-administered questionnaire and interviews with South African banks and insurers were attained by factor analyses, Mann- Whitney U tests and Step-wise discriminant function analysis, It was found that successful projects are; synergistic with the fum's resources and skills, they embody a competitive advantage and rely on a degree of service newness that is not too uncomfortable for consumers, they are also developed with insight into consumer's behaviour. Banks are better at conducting detailed prediction studies than insurers. Comparatively, insurers are better at integrating cross-functionally all the necessary departments. Step-wise discriminant analysis revealed sales growth and profit objectives to be the performance measurements that significantly predict and classify new successful services. No factors for failed service products were found. Limitations of the research are acknowledged and suggestions are made for further research into the topic.
A dissertation submitted to the Faculty of Commerce, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters in Business Economics
Keywords: Banks and banking -- South Africa; Insurance -- South Africa